The Influence of Organizational Culture and Emotional Intelligence on Employee Performance at the Satpol PP of Cirebon Regency - Suci Nuraeni; Feny Risqi Yanti; Bachrudin Syahroni; Moh Yudi Mahadianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study was to analyze the role of organizational culture and emotional intelligence on employee performance at the Civil Service Police Unit of Cirebon Regency. Quantitative research with a survey approach and regression analysis. The method used in this study was a survey with a quantitative approach. Data were obtained from 159 employees of the Cirebon Regency Civil Service Police Unit through randomly selected questionnaires. With hypothesis testing using multiple linear regression analysis. The results showed that the influence of organizational culture has a positive and significantly greater influence on employee performance compared to emotional intelligence. Explain your limitations here. Organizations, especially Civil Service Police Units, need to improve and pay attention to organizational culture and employee emotional intelligence to improve performance. Training and development programs that focus on both aspects can be implemented. The information provided in this study is about the influence of organizational culture and emotional intelligence on employee performance in the public sector, especially Civil Service Police Units. It is hoped that this study can be a reference for further research with different variables and contexts.